2020
DOI: 10.3390/biology9030042
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on Body Size and Abundance Relationships across Ecological Communities

Abstract: Recently, several studies have reported relationships between the abundance of organisms in an ecological community and their mean body size (called cross-community scaling relationships: CCSRs) that can be described by simple power functions. A primary focus of these studies has been on the scaling exponent (slope) and whether it approximates −3/4, as predicted by Damuth’s rule and the metabolic theory in ecology. However, some CCSR studies have reported scaling exponents significantly different from the theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
1
8
1
Order By: Relevance
“…The patterns of the LSDR across the two floodplain channels, considering the whole dataset including all the months, were both statistically significant, with similar slopes (i.e., −0.39 and −0.33 for MOLO and PONT, respectively) that were significantly shallower than predicted by Damuth [8][9][10]. Our patterns were consistent with several studies that suggested that the relationship between body size and abundance is much shallower than the value of −0.75 for aquatic macroinvertebrate communities (e.g., [26,[50][51][52]) and other animal communities (e.g., [19,[53][54][55][56]). However, the shallower slopes found were not consistent with the EER.…”
Section: Patterns Of Lsdr Molo and Lsdr Pont (All Months Included)supporting
confidence: 89%
“…The patterns of the LSDR across the two floodplain channels, considering the whole dataset including all the months, were both statistically significant, with similar slopes (i.e., −0.39 and −0.33 for MOLO and PONT, respectively) that were significantly shallower than predicted by Damuth [8][9][10]. Our patterns were consistent with several studies that suggested that the relationship between body size and abundance is much shallower than the value of −0.75 for aquatic macroinvertebrate communities (e.g., [26,[50][51][52]) and other animal communities (e.g., [19,[53][54][55][56]). However, the shallower slopes found were not consistent with the EER.…”
Section: Patterns Of Lsdr Molo and Lsdr Pont (All Months Included)supporting
confidence: 89%
“…Genome size does not always determine cell size, thus opening up the possibility that cell (or propagule) size may first change and only later through evolution be accompanied by changes in genome size. Increases in both cell size and genome size (including polyploidy) along natural environmental gradients of decreasing temperature, as observed in various protists, plants and invertebrate animals (e.g., [ 9 , 56 , 61 , 62 , 103 , 182 , 191 , 192 , 276 , 280 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 ]; but see [ 90 , 118 , 172 , 183 , 193 , 305 ]), may be the result of long-term adaptive evolution. If so, they (in combination with the laboratory experiments of [ 290 ]) provide support for the hypothetical view described in Section 4.4.2 ( Figure 6 ) that, on an evolutionary timescale, changes in cell size may precede changes in genome size (also see next Section 4.7 ).…”
Section: Discussionmentioning
confidence: 99%
“…rocky intertidal assemblages, stream insects, rainforest birds, desert lizards, large grazing mammals, pelagic zooplankton, or coral reef fishes), sometimes referred to as ‘horizontal communities’ (Vellend, 2016). While body size can still be an important predictor of competitive interactions in horizontal communities (Gjoni & Glazier, 2020), it has comparatively lower potential to elucidate patterns of community assembly or their effects on functioning, since there is little variation among species for investigators to exploit (Brown et al ., 2018). In other words, community ecologists are predominantly concerned with niche differences beyond body size, which is evident in the residual variation of species' MRs around the paradigmatic correlation with body size (the ‘noise’ around the universal relationship) ( cf .…”
Section: Metabolic Traits To Enumerate Animal Community Assembly and ...mentioning
confidence: 99%